Botryosphaeriaceae associated with die‐back of Schizolobium parahyba trees in South Africa and Ecuador. Issue 5 (12th May 2014) - Mehl, J. W. M.; Slippers, B.; Roux, J.; Wingfield, M. J.; Sieber, T.
Summary Die‐back of Schizolobium parahyba var. amazonicum is a serious problem in plantations of these trees in Ecuador. Similar symptoms have also been observed on trees of this species in various parts of South Africa. The most common fungi isolated from disease symptoms on S. parahyba var. amazonicum in both locations were species of the Botryosphaeriaceae. The aim of this study was to identify these fungi from both Ecuador and South Africa, and to test their pathogenicity in greenhouse and field trials. Isolates obtained were grouped based on culture morphology and identified using comparisons of DNA sequence data for the internal transcribed spacer (ITS) and translation elongation factor 1α (TEF‐1α) gene regions. The β‐tubulin‐2 (BT2) locus was also sequenced for some isolates where identification was difficult. Three greenhouse trials were conducted in South Africa along with a field trial in Ecuador. Neofusicoccum parvum was obtained from trees in both areas and was the dominant taxon in South Africa. Lasiodiplodia theobromae was the dominant taxon in Ecuador, probably due to the subtropical climate in the area. Isolates of Neofusicoccum vitifusiforme (from South Africa only), Neofusicoccum umdonicola and Lasiodiplodia pseudotheobromae (from Ecuador only) were also obtained. All isolates used in the pathogenicity trials produced lesions on inoculated plants, suggesting that the Botryosphaeriaceae contribute to the die‐back of S. parahyba trees. While the disease is clearly not caused by a single species of the Botryosphaeriaceae in either region, N. parvum has been introduced into at least one of the regions. This species has a broad host range and could have been introduced on other hosts.